Depth-dependent structural analysis of polyolefin multilayer films using microbeam X-ray diffraction - Junsu Kim; Seungjae Lee; Mingeun Park; Yehyun Kim; Nam-Joon Cho; Hyungju Ahn; Du Yeol Ryu (Polymer Testing)
Recent tightening of global regulations on plastic waste treatment has promoted the use of single type materials (over 95 %) with similar chemical identities. To meet such a mono-material regulation for upcycling and downcycling, polyolefin (PO) multilayer films comprising polyethylene (PE) and polypropylene (PP) have been most widely fabricated with the other functional layers because of their complementary physicochemical properties. To characterize depth-dependent compositional and structural properties of the PO multilayer films, we propose an analytical integration of a focused ion beam with scanning electron microscopy (FIB-SEM) technique and synchrotron microbeam wide-angle x-ray diffraction (M-WAXD). The two types of PE/(PE + PP)/PE and PP/PE/PP multilayer films were sequentially step-milled using the FIB-SEM, which enabled the high-resolution depth control of the films. The step-milled sculptures of multilayer films were exposed normal to microbeam x-rays in a transmission-mode, providing insights into the composition, nanoparticle dispersion, and crystal orientation as a function of film thickness. Our results highlight the analytical capability using an effective combination of FIB-SEM technique and M-WAXD, pointing out the importance of depth-dependent structural analysis for mono-material PO multilayer films.